2021
DOI: 10.1088/1742-6596/2124/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Research results of solid particle erosion resistance of 20GL steel with boriding

Abstract: The paper presents the results of experimental studies of solid particle erosion resistance of 20GL structural steel samples with two different variants of surface modification based on the boriding process. Characteristics of modified layers such as depth, composition, microhardness were determined. Tests were carried out according to ASTM G76-13 standard at air-abrasive flow rate of 170 m/s, flow attack angles of 30º and 90°, sample surface temperature of 25ºC. It was found that both considered options of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In comparison with earlier studies of solid particle erosion resistance for 20 GL steel with boriding [102], this work revealed a significant increase in the wear intensity for 30 L steel samples with boriding. This may be due to an increased percentage (%) of carbon C: 30 L steel (0.27-0.35) and 20 GL steel (0.15-0.25) [101] and/or a decrease in the percentage (%) of manganese Mn: 30 L steel (0.4-0.9) and 20 GL steel (1.2-1.6) [101].…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…In comparison with earlier studies of solid particle erosion resistance for 20 GL steel with boriding [102], this work revealed a significant increase in the wear intensity for 30 L steel samples with boriding. This may be due to an increased percentage (%) of carbon C: 30 L steel (0.27-0.35) and 20 GL steel (0.15-0.25) [101] and/or a decrease in the percentage (%) of manganese Mn: 30 L steel (0.4-0.9) and 20 GL steel (1.2-1.6) [101].…”
Section: Resultssupporting
confidence: 60%
“…The research results demonstrated that boriding processes worsen the solid particle erosion resistance of 30 L steel at flow angles of 30 and 90 degrees due to embrittlement of the surface. In turn, the previously obtained data [102] on the multiple increase in solid particle erosion resistance of 20 GL steel with boriding indicate a significant influence of the chemical composition of steel, in particular the percentage of carbon and manganese, on the strength characteristics of the surface after boriding.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The results in [35] indicate that the boriding process of hydraulic machine parts made of steel 20GL will improve their solid particle erosion resistance and extend their overhaul period.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, a team of authors conducted research on the solid particle erosion resistance of borided 20GL steel samples [35]. The chemical composition of steel 20GL is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%